Comparative assessment on the extraction of carotenoids from microalgal sources: Astaxanthin from H. pluvialis and β-carotene from D. salina. (30th March 2019) - Rammuni, M.N.; Ariyadasa, Thilini U.; Nimarshana, P.H.V.; Attalage, R.A.
Highlights: Astaxanthin and β-carotene have the highest demand in global carotenoid market. Solvent extraction provides the highest productivity in carotenoid extraction. Pretreatment methods have a significant impact on recovery percentage of carotenoid. Bio refinery routes are cost effective and efficient to use in industrial scale. Microalga based bio refineries have higher productivity than conventional methods. Abstract: Astaxanthin and β-carotene are important carotenoids used in numerous pharmaceutical and nutraceutical applications, owing to their vigorous antioxidant properties. The microalgal strains Haematococcus pluvialis and Dunaliella salina accumulate the highest quantities of astaxanthin and β-carotene (up to 7% and 13% dry weight respectively) and are therefore considered as sustainable feedstock for the commercial production of carotenoids. Thus, from an economical perspective, it becomes desirable to optimize recovery of carotenoids from microalgal cells. To this end, here, we have summarized the conventional and modern extraction techniques generally used for the recovery of astaxanthin from Haematococcus pluvialis and β-carotene from Dunaliella salina . Furthermore, we have also discussed the optimum process conditions employed for numerous extraction protocols including solvent extraction, ultrasonic-assisted extraction (UAE), microwave-assisted extraction (MAE) and supercritical fluid extraction (SFE). Overall, our study highlights the sustainability of integrated co-production of biofuels and carotenoids in a biorefinery framework.